Taming the Renewables: Actors’ Innovation in Improving the Utilisation of Biogas for Everyday Use in Agricultural Setting - Alam, Meredian (International Journal of Renewable Energy Development, 2016)
Biogas development in Indonesia has reached a large number of users since 2009 and the technology has had a successful adoption rate at the local level. However, the ways that users develop and adopt innovation with regards to this useful technology has been under-researched. This study aims to address the innovations being undertaken by biogas users; these innovations are a decentralising process of technical knowledge that is based on users’ interpretations of pre-existing social and cultural values they experience in everyday life. Through innovation, users can demonstrate a greater sense of ownership, which leads to them feeling more able to integrate the biogas into their lives, including its incorporation into agricultural activities at home. The main recommendation drawn from this research is that users’ ideas and knowledge, as well as the social-cultural values underlying their everyday lives, should be taken into account in order to ensure successful construction processes and that they be understood as co-shaping elements that will enable a smooth immersion of the users and the technology.Article History: Received November 26th 2015; Received in revised form January 15th 2016; Accepted January 26th 2016; Available online How to Cite This Article: Alam, M. (2016) Taming the Renewables: Actors’ Innovation in Improving the Utilisation of Biogas for Daily Use in Agricultural Setting. Int. Journal of Renewable Energy Development, 5(1),57-64 . http://dx.doi.org/10.14710/ijred.5.1.57-64